Therapeutic role of Thymol, Propolis and Balanites aegyptiaca against experimental Toxocara vitulorum infection - Huda Mohammed Kuraa; Malek S. S.; Abdel-Rahman I. A. M. I. A. M.; El Hendy A. H. M. (Veterinary Integrative Sciences)
Toxocara vitulorum (T. vitulorum) is a significant intestinal nematode that has led to a large global economic loss for farm animals. While there is a paucity of safe and effective anthelmintic drug development against it. Thus, this work aimed to estimate the antiparasitic effect of Thymol, Balanites aegyptiaca (B. aegyptiaca), and propolis as an alternative treatments against T. vitulorum larvae in vivo. To achieve this purpose, the embryonation of T. vitulorum eggs were done in vitro. Then, a total of thirty female wester rats were divided into six groups (5 each). Infected rats were orally inoculated by 2500 eggs containing third stage larvae. These groups were (control negative), (control positive), treated with (piperazine citrate 300 mg/kg), (thymol 40 mg/kg), (B. aegyptiaca 250 mg/kg), and (propolis 100 mg/kg). Parasitological and histopathological responses of all treated groups were evaluated at 7 and 14 days post infection (dpi). Microscopical examination of lung, liver (pepsin digested organs) and brain (squashed method) were used for counting of larvae. The numbers of larvae reduced at 14 dpi and accomplished the highest reduction in Thymol group (75%) followed by Propolis group (55.8%) and B. aegyptiaca group (53.8%) than in control positive group. Histopathological examination proved that thymol followed by propolis and B. aegyptiaca extracts were effective in improving the pathological changes and had a good effect on organ damage protection that was caused by T. vitulorum larvae. So, they can be used as an alternative, safe, and effective treatment of T. vitulorum infection.